Kerjasama Guru dan Orang Tua dalam Membentuk Karakter Disiplin Siswa SMAN 1 Lembah Gumanti - Elfina Camelisa; Firman Firman; Rusdinal Rusdinal (Syntax Idea, 2021)
The purpose of this study is to describe how schools should shape the characteristics of social care in students of SMAN 1 Lembah Gumanti. This research is motivated by a lack of understanding of the importance of subjects in students and parents, so a cooperative relationship between parents and teachers is needed to shape student subjects. Types of research used with data collection techniques in descriptive and qualitative form such as observations, interviews, and library studies. This study describes and shows the fact that teachers have worked hard to work with parents, among others: fostering good relationships between parents and teachers, providing direction and learning about character education, including parents in this character education program, then also giving birth to a mutual agreement between teachers and parents about the limitations of the use of gadgets and social media for students. Coordinate teacher visits to students' homes to further monitor the policies that have been made. With the active role of both parties between teachers and parents is expected to realize the program of character building of the students